Sex ratios: human twins and fraternal effects. - Knowles, S; Sheldon, B (2007)
Historical data from Finnish populations reveals that, for females, exposure to a male twin in the womb may have significant, life-long, effects on subsequent fitness, with profound implications for the evolution of sex ratios and brood size.